2021
DOI: 10.1007/s00508-021-01917-9
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil to lymphocyte ratio is an independent predictor for severe COVID-19

Abstract: Summary Purpose The aim of this study was to determine whether the neutrophil to lymphocyte ratio (NLR) can predict severe Coronavirus disease 2019 (COVID-19). Patients and methods A multicenter case-control study was conducted to investigate whether the NLR can help predict the severity of COVID-19. Patients confirmed to have COVID-19 between 16 January 2020 and 15 March 2020 were enrolled. Furthermore, meta-analyses were conducted based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We did not find any significant association of any clinical features with the BMI category. A previous study from Bangladesh did not find any significant association between different BMI categories with patients categorized based on symptoms 12 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We did not find any significant association of any clinical features with the BMI category. A previous study from Bangladesh did not find any significant association between different BMI categories with patients categorized based on symptoms 12 .…”
Section: Discussionmentioning
confidence: 71%
“…Neutrophilia along with lymphopenia which is the elevated neutrophils/lymphocytes ratio is one of the independent risk factors of severe COVID-19 and poor outcome 12,13 . Around 75% of deceased Bangladeshi hospitalized COVID-19 patients had also high NLR (e"5) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis conducted by Cheng et al (2021), which analyzed 17 studies and 7,049 COVID-19 patients, it was found that the NLR (neutrophil-to-lymphocyte ratio) was significantly higher in patients with severe COVID-19 compared to those with non-severe COVID-19 [ 44 ]. This study reinforces that the initial NLR can be a reliable predictor of severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline characteristics of the non-ARDS group and ARDS group are listed.The cut off value of NLR for moderate-severe ARDS is 11.The high NLR group (NLR > 9.8) showed a higher incidence of ARDS (P= 0.005) and higher rate of non-invasive (P= 0.002) and invasive (P= 0.048)mechanical ventilation. InWenjing Ye1et al study27 they studied the dynamic changes in NLR in 349 patients at the time of joining in the hospital and few days after the admission they found that association between clinical deterioration and changes in NLR values as follows Initial NLR in survivors 2.88(1.79-6.74), in dead patients it is about 14.96(8.52-26.58) with P-value <0.001. Peak NLR changes as follows in survivors 4.14(2.11-12.32), in dead patients it is about 46.58(27.95-87.29) with p-VALUE <0.001.…”
mentioning
confidence: 99%